EMPOWERMENT OF THE TAPAK GEDUNG VILLAGE COMMUNITY IN KEPAHIANG REGENCY (BENGKULU) THROUGH PROCESSING ORGANIC WASTE INTO A MULTIPURPOSE ECO-ENZYME - Jumiarni, Dewi; Murniati, Neni; Alfra Siagian, Teddy (LPPM Univ. Ibn Khaldun Bogor, 2023)
Tapak Gedung Village, Kepahiang Regency (Bengkulu) has a problem with waste. So far, the organic waste produced by the community is simply thrown away into the surrounding environment. One alternative solution that can be done to reduce environmental pollution caused by organic waste is to manage the organic waste into a multipurpose eco-enzyme. This community service activity is carried out with the aim of increasing the understanding and skills of the Tapak Gedung Village community in making multipurpose eco-enzymes. The activity method is carried out in several stages, namely training, mentoring, monitoring and evaluation. This activity was carried out in August 2022 with 30 participants. The results of the activity evaluation showed that this activity had increased the participants' understanding and skills in making eco-enzymes with an N-gain of 0.85 or high criteria, which means that this activity was effective. The results of the training participant satisfaction survey showed that the activity participants were satisfied with the activities carried out and felt that the activities provided were appropriate according to the needs of the community.